Pelatihan Kewirausahaan “Menerapkan Strategi Pemasaran Yang Efektif Agar Produk Kerajinan Tangan Yang Dihasilkan Diterima Pasar” (Panti Asuhan Annisa, Pekanbaru, Riau) - Dewi Martha; Indah Intani; Rizkinisa Afsyah; Rodiatun Mukarama; Susi Aritonang; Yurike Milenia (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2022)
Handicraft is an artistic activity that focuses on hand skills and functions to process raw materials that are often found in the environment into objects that are not only of use value but also of aesthetic value. In the Community Service (PKM) activity of STIE Mahaputra Riau, lecturers and students involved in this activity came directly to the Annisa Pekanbaru Orphanage to provide training on making handicrafts with simple ingredients to produce handicraft products that have a high selling value in the market, conduct discussions , questions and answers and counseling about effective marketing strategies to market the handicraft products produced as well as providing motivation about the concepts and benefits of entrepreneurship for school-age children at the Annisa Orphanage Pekanbaru. This PKM activity aims to generate and foster an interest in entrepreneurship for school-age children at the Annisa Orphanage, Pekanbaru, Riau, so that they are motivated to realize their own business or business independently and succeed with their own business by engaging in the handicraft business.